2007
DOI: 10.1017/s0265021507000804
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the laryngeal tube-S™ and Proseal™ laryngeal mask during outpatient surgical procedures

Abstract: Both devices provide a secure airway, are similar in clinical utility and are easy to insert. Better airway seal was detected in the PLMA group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
(28 reference statements)
0
4
1
1
Order By: Relevance
“…The vocal cords were visible (grade I to II) in 25% and 33.3% in the LTS-D and LTS-II groups respectively. Fiberoptic view of the vocal cords were considerably lower than reported in the literature 5,21 . The cause of this difference is unclear but LTS has two smaller medial orifices.…”
Section: Discussioncontrasting
confidence: 57%
“…The vocal cords were visible (grade I to II) in 25% and 33.3% in the LTS-D and LTS-II groups respectively. Fiberoptic view of the vocal cords were considerably lower than reported in the literature 5,21 . The cause of this difference is unclear but LTS has two smaller medial orifices.…”
Section: Discussioncontrasting
confidence: 57%
“…Physicians employed the laryngeal tube during scheduled anaesthesia in 36 studies [2256] with a total of 1,897 patients: the first-pass insertion success rate of these providers was 82.5% (1,452/1,760, 95% CI: 80.7%–84.3%), and the overall-pass insertion success rate was 93.6% (1,594/1,703) (95% CI: 92.4%–94.8%, p < 0.001) (Table 1). Paramedics, paramedic students, and BLS nurses employed the laryngeal tube in an in-hospital setting in 4 studies [5760] including 151 patients.…”
Section: Resultsmentioning
confidence: 99%
“…also found that the OSP of PLMA was higher than that of LTS-II. [16] However, Brimacombe et al . found no difference in OSP between LTS-II and PLMA, in adult patients.…”
Section: Discussionmentioning
confidence: 99%